The pathogenic mechanism of oral bacteria and treatment with inhibitors - Thuraya Elgreu; Sean Lee; Sabrina Wen; Radwa Elghadafi; Thanarut Tangkham; Yun Ma; Bing Liu; Serge Dibart; Xiaoren Tang (Wiley, 2022)
Abstract Objectives The objective of this study was to introduce the evidence obtained through extensive research that periodontitis increases risk of many systemic diseases. Method Analysis of some oral bacteria (P. gingivalis, T. denticola, T. forsythia, A. actinomycetemcomitans, and F. nucleatum) and its related treatments and mediators by the specific methods (western blot, ELISA, etc). Results This article reviews in detail the evidence obtained through extensive research that periodontitis increases risk of many systemic diseases, including cardiovascular disease, rheumatoid arthritis, and Alzheimer's disease. These diseases are known to be associated with some certain specific gram‐negative bacteria as periodontal pathogens, which induce inflammation and related diseases through TLR receptors, kinases, transcriptional factors and other cytokines. We also reviewed the latest research for inhibitors against inflammation and related diseases that have potential to be further applied clinically. In addition, based on a large amount of research evidence, we draw two tables about the mechanism of disease caused by periodontal bacteria, so that readers can easily search and analyze these research results. Discussion This review details how the periodontal bacteria and their virulence factors can trigger host immune defense and induce many systemic diseases via inflammation and invasion. This Review also addressed the latest research around inhibitors against inflammation.